A Cloud Model-Based Evaluation of Renovation Decisions for Old Urban Communities from the Perspective of Resilience—A Case Study of a Community in Nanjing, China - Xisheng Li; Xiang Zhang; Jiaying Zhang (Buildings, 2025)
The renovation of old communities is a major measure taken to promote urban development and transformation and can improve the quality of urban space and the living environment of residents, as well as promote economic development and bring new economic growth to the city. Decision-making regarding the updating of old communities is the starting point of the whole renovation process, and can be classified into two aspects: resilience assessment and renewal-potential evaluation. In order to standardize the retrofit evaluation index system, enhance the guidance of renovation decision plans for community renewal practices, and consider the randomness of evaluation indicators and the visualization of evaluation results, this paper proposes a method for evaluating the potential of old-urban-community renovation from the perspective of resilience. Based on an analysis of the relationship of the PSR (pressure–state–response) model and community resilience, as well as literature statistics, an evaluation index for the potential of old-community renovation according to the PSR model is established. Furthermore, vague set theory is applied to reduce the initial evaluation index system; then, entropy weight and the g1 method are used to determine objective and subjective weights, respectively, before determining the combination weight value. And the cloud model comprehensive evaluation method is applied to determine the membership degrees of resilience levels for the indicator, sub-criteria, criteria, and target layer in sequence. Finally, taking Nanjing Yinlun Garden Community as an example, the proposed method is adopted to identify the community’s resilience and renovation priorities, verifying the applicability of the method.